Going public via special purpose acquisition companies: Frogs do not turn into princes - Kolb, Johannes; Tykvová, Tereza (Journal of Corporate Finance, 2016)
Special purpose acquisition companies (SPACs) are cash shells that try to buy private operating firms to which they confer a public-listing status. Private operating firms tend to use SPACs as an alternative way to get listed, particularly in years with weak IPO activity and volatile markets, such as 2008 and 2009. In these two years, approximately 31% of firms went public through a SPAC acquisition rather than through an IPO. Our results from the analysis of 127 SPAC acquisitions and 1128 IPOs during the wave of “new-generation” SPACs starting in 2003 lend support to the conjecture that particular small and levered firms with low growth opportunities tend to use this vehicle. SPAC acquisitions also may be fueled by the cash-out motives of existing shareholders. Venture capitalists and private equity investors tend to refrain from using SPAC acquisitions as an exit route. Tracking long-term abnormal returns, we find that SPAC firms are associated with severe underperformance in comparison to the market, the industry and (comparable) IPO firms.